Maternal near misses from two referral hospitals in Uganda: a prospective cohort study on incidence, determinants and prognostic factors. Issue 1 (December 2016) - Nakimuli, Annettee; Nakubulwa, Sarah; Kakaire, Othman; Osinde, Michael; Mbalinda, Scovia; Nabirye, Rose; Kakande, Nelson; Kaye, Dan
Abstract Background Maternal near misses occur more often than maternal deaths and could enable more comprehensive analysis of risk factors, short-term outcomes and prognostic factors of complications during pregnancy and childbirth. The study determined the incidence, determinants and prognostic factors of severe maternal outcomes (near miss or maternal death) in two referral hospitals in Uganda. Methods A prospective cohort study was conducted between March 1, 2013 and February 28, 2014, where cases of severe pregnancy and childbirth complications were included. The clinical conditions included abortion-related complications, obstetric haemorrhage, hypertensive disorders, obstructed labour, infection and pregnancy-specific complications such as febrile illness, anemia and premature rupture of membranes. Near miss cases were defined according to the WHO criteria. Multivariate logistic regression analysis was conducted to identify prognostic factors for severe maternal outcomes. Results Of 3100 women with severe obstetric complications, 130 (4.2 %) were maternal deaths and 695 (22.7 %) were near miss cases. Severe pre-eclampsia was the commonest morbidity (incidence ratio (IR) 7.0 %, case-fatality rate (CFR) 2.3 %), followed by postpartum haemorrhage (IR 6.7 %, CFR 7.2 %). Uterine rupture (IR 5.5 %) caused the highest CFR (17.9 %), followed by eclampsia (IR 0.4 %, CFR 17.8 %). The three groups (maternal deaths, near misses and non-life-threatening obstetric complications) differed significantly regarding gravidity and education level. The commonest diagnostic criteria for maternal near miss were admission to the high dependency unit (HDU) or to the intensive care unit (ICU). Thrombocytopenia, circulatory collapse, referral to a more specialized unit, intubation unrelated to anaesthesia, and cardiopulmonary resuscitation were predictive of maternal death (p < 0.05). Gravidity (ARR 1.4, 95 % C1 1.0–1.2); elevated serum lactate levels (ARR 4.5, 95 % CI 2.3–8.7); intubation for conditions unrelated to general anaesthesia (ARR 2.6 (95 % CI 1.2–5.7), cardiovascular collapse (ARR 4.9, 95 % CI 2.5–9.5); transfusion of 4 or more units of blood (ARR 1.9, 95 % CI 1.1–3.1); being an emergency referral (ARR 2.6, 95 % CI 1.2–5.6); and need for cardiopulmonary resuscitation (ARR 6.1, 95 % CI 3.2–11.7), were prognostic factors. Conclusions The analysis of near misses is a useful tool in the investigation of severe maternal morbidity. The prognostic factors for maternal death, if instituted, might save many women with obstetric complications.